Characteristics associated with attending community-based versus clinic-based HIV testing services among overseas-born gay, bisexual, and men who have sex with men in Sydney, Australia - Rebecca Houghton; Anik Ray; Alison Mahony; Lisa McCann; Brent Mackie; Joubert van der Merwe; Rick Varma; Arthur Wong (Sexual Health, 2026)
Background Overseas-born gay, bisexual, and other men who have sex with men (GBMSM) experience higher HIV notification rates compared with Australian-born GBMSM. This disparity is perpetuated by delayed access to HIV testing and biomedical prevention driven by a range of factors including Medicare eligibility, language and cultural barriers, and unfamiliarity with the health system. Community-based services offer an alternative pathway to HIV testing that may better serve migrant GBMSM facing challenges accessing mainstream healthcare settings. Methods We conducted a cross-sectional study comparing settings of first HIV test within our service, either peer-led community-based testing or traditional clinic-based testing for overseas-born GBMSM who arrived in Australia between January 2022 and January 2024. Participants were grouped by time of arrival to first HIV test (either less than 6 months or more than 6 months). Comparative analysis and multivariable logistic regression were used to identify characteristics associated with attendance at the community-based setting. Results A total of 1204 GBMSM were included with 424 (35.2%) attending community-based setting for their first HIV test after arrival. Those who attended community-based testing were more likely to have arrived in Australia more than 6 months ago (66.8% vs 26.9%) and never previously tested for HIV (37.5% vs 17.2%). These factors were also associated with higher likelihood of community-based testing in the multivariable model (aOR 5.27, 95% CI 3.98–6.97 and aOR 2.13, 95% CI 1.57–2.91 respectively). Conclusion Community-based, peer-led HIV testing services play an important role in engaging overseas-born GBMSM who may be under-served by traditional clinic-based models, particularly those with longer residence in Australia and no prior HIV testing.